Magnetic fields in food processing perspectives, applications and action models - Miñano H.L.A. (2020)
Magnetic fields (MF) are increasingly being applied in food processing to preserve food quality. They can be static (SMF), oscillating (OMF) or pulsed (PMF) depending on the type of equipment. The food characteristics can be influenced by several configurations of the applied magnetic field as its flux density, frequency, polarity and exposure time. Several mechanisms have been proposed to explain the eects of magnetic fields on foods. Some of them propose interactions at the subatomic particle level that show quantum behavior, such as the radical pair and cyclotron resonance mechanisms. Other proposals are at the level of DNA, compounds, subcellular organelles and cells. The interactions between food and magnetic fields are addressed in a general way in this work, highlighting the applications and action models involved and their eects on the physicochemical, enzymatic and microbiological characteristics of food. © 2020 by the authors.